2010
DOI: 10.2202/1944-2866.1040
|View full text |Cite
|
Sign up to set email alerts
|

Agenda Setting in a Digital Age: Tracking Attention to California Proposition 8 in Social Media, Online News and Conventional News

Abstract: This study compares the agenda‐setting cues of traditional media alongside those of online media in general and social media in particular. The main line of inquiry concerns (a) whether people posting content to openly accessible social media outlets may be acting in response to mainstream news coverage, possibly as a “corrective” to perceived imbalances in that coverage, or (b) whether such posts seem to have influenced professional media coverage of the issue, possibly reflecting broader opinion dynamics. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
106
0
8

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(127 citation statements)
references
References 37 publications
5
106
0
8
Order By: Relevance
“…Altogether, there is fairly clear evidence from previous studies that the SNSs can be important intermedia agenda-setting agents, particularly because of their capacity to quickly and easily share stories and break news as it occurs [21,23,28,29]. Considering the intersection of these findings with that of previous work on focusing events [30] and live-event news [31], it seems clear that agenda setting has reached a conceptual and empirical juncture [24].…”
Section: Agenda Setting From Mass Media Through Social Mediamentioning
confidence: 70%
See 3 more Smart Citations
“…Altogether, there is fairly clear evidence from previous studies that the SNSs can be important intermedia agenda-setting agents, particularly because of their capacity to quickly and easily share stories and break news as it occurs [21,23,28,29]. Considering the intersection of these findings with that of previous work on focusing events [30] and live-event news [31], it seems clear that agenda setting has reached a conceptual and empirical juncture [24].…”
Section: Agenda Setting From Mass Media Through Social Mediamentioning
confidence: 70%
“…Accordingly, as Sayre and colleagues reported, "the Internet is at the center of this change, expanding the definition of news sources and news producers" [21]. Without question, the rise of the media "produser," as described by Bruns [9] has altered conceptions of where media agendas begin and end in relation to the public agenda.…”
Section: Agenda Setting From Mass Media Through Social Mediamentioning
confidence: 99%
See 2 more Smart Citations
“…Groshek and Clough Groshek maintain "that there are still fairly clear intermedia agendasetting effects of traditional media on social networking sites, but that influence is not uniform across topics or the social media channels." (Groshek and Clough Groshek 2013, 21; see also Sayre et al 2010) Even during occurrences in which the role of social media was deemed to be of immense importance, as were the events of the so-called Arab Spring, a closer look showed that routine sources prevailed in reporting (Knight 2012, 68;Bashri et al 2012) The potential of new media to set the agenda thus appears to be circumscribed by the conservative forces in journalism, be it workplace routines or the values of editors, i.e. the aspects of journalism as a profession.…”
Section: Social Media: a Routine Or An Exceptional Source?mentioning
confidence: 99%